STUDI KORELASI KEMAMPUAN BAHASA ARAB DAN PROSES PEMBELAJARAN TERHADAP KEMAMPUAN SISWA MENGUASAI MATERI HADITS SISWA KELAS XII MAN 1 JAKARTA - Sarno Hanipudin (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
This research has the background of the idea that Arabic is a universal language, including in the context of Islam. Because in Islam, almost half of the sources of history, law and other Islamic sciences are in Arabic. This is no exception to the Hadith, which is one of the sources of Islamic law as well as a way of knowing the history of the prophet Muhammad SAW. In the context of Islamic education, Arabic language proficiency is the minimum standard that must be mastered by students, because it will be difficult if a student does not master Arabic. This study aims to determine whether there is a relationship between Arabic Language Ability and the Learning Process of Students' Ability to Master the Hadith Material of case study grade 3 students at Madrasah Aliyah Negeri 1 Jalan Rawa Bahagia 1/28 West Jakarta. Keywords: Arabic, Hadith Lesson, MAN 1 Jakarta